Naprava s pnevmatično aktivno površino: Tehnike krmiljenja gibljivih predmetov - Uran, Suzana (Strojniški vestnik, 2002)
The current lack of manufacturing techniques for very-high-volume handling of small objects presents a technology barrier to commercial success in various fields like micro-electromechanical systems (MEMS). A fundamentally new approach to automated, massive, parallel manipulation of small-sized parts is explored in this paper. We have investigated a pneumatic active-surface device (PASD) that offers great flexibility and simultaneous control of several objects. By either blowing or sucking air through the tubes of the PASD we can cause objects placed on the array to be moved in useful ways.This paper describes our experimental work on a prototype PASD. Open-loop control for translation in two degrees of freedom and the rotation of flexible objects on a PASD are considered. Due to disturbances that cause deviations to the desired motion, open-loop translation control with closed-loop rotation control was also developed.
Keywords: deli mali; rokovanje s predmeti; naprave pnevmatične; zaznavanje predmetov; krmiljenje; strojni elementi; majhni predmeti; avtomatizacija; manipulacija; pnevmatske naprave